2014
DOI: 10.18632/oncotarget.3087
|View full text |Cite
|
Sign up to set email alerts
|

KITENIN promotes glioma invasiveness and progression, associated with the induction of EMT and stemness markers

Abstract: KITENIN (KAI1 COOH-terminal interacting tetraspanin) promotes tumor invasion and metastasis in various cancers. This study assessed the association between KITENIN expression and advanced glioma grade in patients. In vitro assays revealed that KITENIN knockdown inhibited the invasion and migration of glioma cells, whereas KITENIN overexpression promoted their invasion and migration. In orthotopic mouse tumor models, mice transplanted with KITENIN-transfected glioma cells had significantly shorter survival than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 49 publications
2
48
0
Order By: Relevance
“…As reported earlier, cyclin D1, VEGFA, SLUG, MMP-9, Bcl-2, bcl-xL, and caspase 3 are involved in regulating glioma cells proliferation, migration, invasion, and apoptosis. [26][27][28][29][30] Meanwhile, STAT3 could promote tumor cells progression via modulating these genes. [31][32][33][34][35][36][37] The expressions of p-STAT3, cyclin D1, VEGFA, SLUG, MMP-9, Bcl-2, and bcl-xL were robustly rescued in miR-384+PIWIL4 (non-3′UTR) group than that in miR-384+PIWIL4 group; the expression of cleaved caspase 3 in miR-384+PIWIL4 (non-3′UTR) group was blocked versus with that in miR-384+PIWIL4 group (Figure 6f).…”
Section: Overexpression Of Mir-384 Hindered Piwil4induced Promotion Omentioning
confidence: 99%
“…As reported earlier, cyclin D1, VEGFA, SLUG, MMP-9, Bcl-2, bcl-xL, and caspase 3 are involved in regulating glioma cells proliferation, migration, invasion, and apoptosis. [26][27][28][29][30] Meanwhile, STAT3 could promote tumor cells progression via modulating these genes. [31][32][33][34][35][36][37] The expressions of p-STAT3, cyclin D1, VEGFA, SLUG, MMP-9, Bcl-2, and bcl-xL were robustly rescued in miR-384+PIWIL4 (non-3′UTR) group than that in miR-384+PIWIL4 group; the expression of cleaved caspase 3 in miR-384+PIWIL4 (non-3′UTR) group was blocked versus with that in miR-384+PIWIL4 group (Figure 6f).…”
Section: Overexpression Of Mir-384 Hindered Piwil4induced Promotion Omentioning
confidence: 99%
“…During the last decades, research has identified CSCs as central players in cancer metastasis. CSCs are a small population of cells responsible for initiation of tumor burden and therapeutic refractoriness . Acquisition of self‐renewal capacity and stemness properties at the time of tumorigenesis is an essential prerequisite for further accumulation of oncogenic transformations and eventual development of cancer .…”
Section: Discussionmentioning
confidence: 99%
“…CSCs are a small population of cells responsible for initiation of tumor burden and therapeutic refractoriness. (27) Acquisition of self-renewal capacity and stemness properties at the time of tumorigenesis is an essential prerequisite for further accumulation of oncogenic transformations and eventual development of cancer. (28) Here, we sought to identify CSC-like cells by inducing ectopic overexpression of CD133 in two PC cell lines (PC3 and DU145).…”
Section: Discussionmentioning
confidence: 99%
“…Since it was demonstrated that CDK10 overexpression affected the metastasis of glioma, further experiments aimed to reveal the underlying mechanism. EMT is considered to be highly relevant to glioma metastasis, which occurs at the invasive front of glioma tissues (18). A previous study demonstrated that the expression status of EMT markers was closely associated with mesenchymal differentiation in gliosarcoma, a rare form of glioblastoma characterized by a biphasic mode of glial and mesenchymal differentiation (22).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that EMT serves a crucial role in the metastasis of various types of cancer. The shift to EMT-associated protein expression is regarded as an important mechanism in the promotion of motility in glioma cancer cells (18,19). Therefore, the expression statuses of EMT protein markers were analyzed by western blot analysis.…”
Section: Cdk10 Regulates Epithelial-mesenchymal Transition (Emt)-assomentioning
confidence: 99%